An Analysis of Illocutionary Act and Context of Situation Found in The Movie “Angela’s Christmas” - Budiantini, Ni Kadek Novita; Pratiwi, Desak Putu Eka (STKIP Agama Hindu Singaraja, 2024)
This research was focused to find out the types of illocutionary acts and analyze the context of the situation in the movie “Angela’s Christmas”. This research used a qualitative method to analyze the types of illocutionary acts with Searle’s (1979) theory and analyze the context of the situation with Halliday and Hasan’s (1989) theory. Meanwhile, also used a quantitative method to show the total data and percentage utterances found in the movie by using a table. The observation method was used to collect the data by watching the movie and note-taking. Based on the results, there were 64 data found, namely assertive consist of 11 data, directive consist of 30 data, commissive consist of 9 data, and expressive consist of 14 data. The most dominant type is directive including 30 data (47%). In this research, the writer did not find one of the categories types of illocutionary acts that is declarative. The implication of this research includes understanding communication strategies and the role of language which is influenced by the context of situation in forming interpersonal relationships in the cartoon movie.